2001
DOI: 10.1046/j.1439-037x.2001.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Moisture and Fertilizer Potassium on the Vegetative Growth of Mungbean (Vigna radiata L. Wilczek) and Cowpea (Vigna unguiculata L. Walp)

Abstract: Tropical food legumes are grown in a wide range of environments, and water stress is considered the principal environmental factor limiting growth and yield. Potassium fertilizer mitigates the impact of water stress in plants. However, the benefits of potassium in overcoming stress in tropical food legumes have not been investigated in comparative studies. The purpose of this study was to determine the benefits of potassium in overcoming water stress in mungbean and cowpea, two important tropical food legumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 18 publications
7
47
0
Order By: Relevance
“…Moreover, well-watered plants produced significantly more leaves in comparison with all other plants, probably because of more profuse branching. This significantly higher vegetative growth of well-watered cut-leaf ground-cherry plants is consistent with the concept found in many other plants of arid environments (including drought-tolerant species) where vegetative growth is significantly enhanced by the supply of adequate soil moisture (Sangakkara et al, 2001;Rahlao et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, well-watered plants produced significantly more leaves in comparison with all other plants, probably because of more profuse branching. This significantly higher vegetative growth of well-watered cut-leaf ground-cherry plants is consistent with the concept found in many other plants of arid environments (including drought-tolerant species) where vegetative growth is significantly enhanced by the supply of adequate soil moisture (Sangakkara et al, 2001;Rahlao et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Potassium is essential for protein synthesis, activation of enzymes and photosynthesis; osmoticum mediating cell expansion and turgor driven movements and competitor of Na + under salt stress (Hu, Schmidhalter, 2005). Several studies have shown that application of potassium mitigates the unfavourable effects of salinity through its role in stomatal regulation, osmoregulation, energy status, charge balance, protein synthesis and homeostasis (Sanjakkara et al, 2001;Mahmood, 2011).…”
Section: Effect Of Potassium On Morphological Physiological and Biocmentioning
confidence: 99%
“…The relative amounts of K + , Ca 2+ , and Mg 2+ increased considerably more in barley than in rye when water stresses were imposed [150]. Potassium contributes to osmotic adjustment as one of the primary osmotic substances in many plant species [161,162] and under water stress conditions, K + application is beneficial for plant survival with improved plant growth [163,164]. There are a few reports indicating that water stress favored increases in K + [147] in plants such as maize [145], drought-tolerant wheat varieties [160], creeping bentgrass [165] and Ammopiptanthus mongolicus (evergreen xerophyte shrub) [166].…”
Section: Drought and Nutrient Uptakementioning
confidence: 99%